Negative childbirth experience in Dutch women: A socio-ecological analysis of individual, interpersonal, and organisational factors from the birth experience study - Tamool A.S. Muhamed; Viola Angelini; Laura Viluma; Hazel Keedle; L. Lilian Peters (Heliyon)
Background: Negative childbirth experience detrimentally impacts women's mental well-being, potentially leading to delaying future pregnancies, and an increased likelihood of requesting caesarean births. Aim: To examine differences between women who reported positive and negative childbirth experience and detangle the complexity of negative childbirth experience by building a socio-ecological model that includes individual, interpersonal, and organisational factors. Methods: We conducted the Birth Experience Study Netherlands (BESt-NL) survey in 2022 with two languages versions (Dutch-English), and incorporated validated measures, such as Mothers' autonomy in decision-making, the Mothers On Respect index, and the Nijmegen Continuity of Care questionnaire. We employed socio-ecological modelling of individual (e.g., sociodemographic, ethnicity, parity, adverse mental health, interpersonal (e.g., autonomy in decision-making, respect, partner support), and organisational factors (e.g., place of birth, continuity of care). We defined negative childbirth experience using the valid Childbirth Experience Questionnaire 2.0. We applied multivariable logistic regression to examine associations between those factors and negative childbirth experience. Findings: In total, (N = 1141) women were included in the BEST-NL study population, and 25 % of women (N = 285) experienced negative childbirth. Higher percentages were observed for non-Dutch ethnicity, preterm births, pregnancy complications, non-spontaneous births, adverse mental health, obstetrician-led care, and low autonomy, respect, social support, and continuity of care. Upon modelling, significant associations emerged i.e., education; or diminished i.e., place of birth; leaving robust associations in preterm, non-spontaneous birth, and adverse mental health, and inverse associations in high autonomy, respect, social support, and continuity of care. Conclusion: Socio-ecological modelling untangled the complexity of negative childbirth experience. This study recommends fostering efforts toward women with prenatal mental health conditions and migrants, emphasises the importance of high autonomy, respect, and continuity in high-quality intrapartum care, and highlights the positive impact of midwife-led care in reducing negative childbirth experience likelihood.